Implementation Of Autogenic Relaxation Techniques to Reduce Pain Scale in Patients With Abdominal Colic - Fauziyyah, Aziizah Nuur; Fitriani, Ade; Purwati, Ayu Endang (KIAN JOURNAL, 2025)
Background: Abdominal colic brings up symptoms of pain that arise and disappear that can interfere with patient comfort, abdominal colic pain is usually accompanied by changes in pulse because the pain is very painful, and causes patients to pay less attention to the conditions around them because patients focus mainly on pain. Therefore, it takes effective treatment to overcome this pain, one of which is non-pharmacological techniques, researchers use autogenic relaxation techniques. Autogenic relaxation technique is a relaxation technique that comes from oneself using short sentences to make the mind calm and comfortable, it can also be called hypnosis to divert pain. Objective: This study is to implement autogenic relaxation techniques to overcome pain. Methods: This case study uses a descriptive method that aims to explore the problem, provide an overview of the case study and analyze more deeply about nursing care by implementing autogenic relaxation techniques to reduce the pain scale in patients with abdominal colic. Results: After implementing autogenic relaxation techniques to reduce the pain scale in patients with abdominal colic for 3 days in the Dahlia room BLUD RSU Kota Banjar, it was proven effective to reduce the pain scale from a scale of 8 to 2, overcome pain, patients said the pain decreased, and seen from the grimace facial expression decreased. Conclusion: the implementation of autogenic relaxation techniques has proven to be effective and very influential to overcome the problem of acute pain in patients with abdominal colic, so that it can be used as nursing care for these patients.